THE INFLUENCE OF TWELVE MONTHS NUTRACEUTICALS AND FUNCTIONAL FOODS INTERVENTION ON AGE AND SEX AS RISK FACTORS FOR IMMUNE SYSTEM (FULafia Journal of Science and Technology, 2017)
Effect of antioxidant functional foods and nutraceuticals on malondialdehyde (MDA) level, cytotoxic clusters of differentiation antigen 4 (CD4) and Immunoglobulin M (IgM) in male and female individuals were studied for twelve months. The volunteers included a total of 150 healthy adults of 96 men and 54 women aged between 30 and 74 years. They were made to sign an informed consent form, questioner and an ethical approval was gotten. At the baseline, eligible candidates were randomized to either 1 capsule per day of antioxidant nutraceutical (Forever living product) (containing vitamin E 10 mg, vitamin C 60mg and β- carotene 2000 mcg of vitamin A, or cheap affordable indigenous antioxidant functional foods of equivalent vitamin composition of oranges, carrots, and soybean or bottled water, and the first dose was dispensed and followed up for six months. There was a positive decrease in MDA and IgM values and a positive increase in CD4 counts after antioxidant dietary intervention. However, a lower concentration of MDA, and higher level of IgM and CD4 in men than in female at some age ranges was observed. The study showed that the indigenous antioxidant functional foods could be used as an alternative to the expensive imported antioxidant nutraceuticals in boosting immunity and therefore suggest such for immune- compromised individuals especially in developing countries like Nigeria
Keywords: Nutraceuticals; functional foods; antioxidant; malondialdehyde; immunoglobulin M; CD4